Evaluación del proceso de elaboración de harina de Musa Paradisiaca (Banano) de rechazo, combinada con harina de Aranas sativus (lindl) Schult (Piña) de rechazo para el consumo humano en el cantón Quevedo - Morales Briones, Karla Belén (2012)
It is important that Ecuador has a great wealth of agricultural products, and unfortunately not utilized properly in spite of containing a highly nutritious and has permanent market demand; the food industry is advancing every day in the development of innovative products that provide nutrients that benefit health. For this reason this research is to solve the general-purpose high rate of post-harvest loss and pineapple bananas today because they do not fully take advantage of it and there is a lot of rejection, and lack of knowledge about their nutritional benefits have, for this reason it won’t make banana flour combined with rejection pineapple flour as an alternative to contributing to the technology industry in Ecuador. The present study was conducted at the Laboratory of Agroindustrial belonging to the State Technical University Quevedo located at Km 1 ½-Santo Domingo route Quevedo, Los Rios Province Canton Quevedo. The work done in this research was to establish the parameters that determine most viable for the production of banana flour combined with pineapple, processes are applied in the laboratory following the techniques established for flour, why was evaluated different percentages of banana flour combined with flour pineapple (s50: 50 and 70:30), different types of antioxidant (1% metabisulfite and 0.5% citric acid).